Study on the effect of heat-input on the thickness of the heat-affected zone of the SUS316L steel welded joint by numerical simulation - Vu, Dinh Toai; Do, Van Long (JST: Engineering And Technology For Sustainable Development, 2021)
The thickness of the heat-affected zone (HAZ) has a great influence on the strength of the welded joint, so one of the important tasks is to control the HAZ to a small enough level, through using the suitable heat-input (qd). In this study, the authors use SYSWELD software to compute and build a relationship between the heat-input and the thickness of the heat-affected zone in the plate thickness direction to find the right heat-input for researched welding joint. The simulation results show that when welding the root pass with qd > 552 J/mm and the cap pass with 754 J/mm